Clinical and Pathological Factors that Affecting the Lymph Node Metastasis in Papillary Thyroid Carcinoma - Zainy , Hayder Mohammed Ali (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Papillary thyroid carcinoma (PTC) is the most common form of thyroid cancer, characterized by its indolent growth and propensity to metastasize to lymph nodes, understanding the factors affecting metastasis in PTC is crucial for improving patient outcomes. Aim of the Study: To evaluate the influence of various clinical and pathological factors on the occurrence of lymph node metastasis (LNM) in patients with PTC. Methodology: A prospective interventional study was conducted at Safeer Al-Imam Al Hussain Surgical Hospital, Imam Hussain medical city, Zain Al-Abedin surgical hospital and Al-Kafeel specialized hospital / Karbalaa/ Iraq over 13 years from 2011-2024, involving 40 patients diagnosed with PTC that underwent total thyroidectomy, and data on demographic, clinical, and pathological variables were collected and evaluated to identify correlations between these variables and N. Results: The mean age of patients was 42.4 ± 12.3 years, with a predominance of females (75%). LNM was observed in 50% of the patients. Significant correlations were found between N and age (p = 0.036), nodule site (p = 0.004), tumor type (p = 0.012), and adjacent lymphatic and vascular invasion (p < 0.001). Older patients, males, patients with nodules in the isthmus or bilateral nodules, and those with multinodular tumors or adjacent lymphatic and vascular invasion had a higher likelihood of LNM. Conclusions: Age, nodule site, tumor type, and adjacent lymphatic and vascular invasion significantly influence N in papillary thyroid carcinoma.
Keywords: Papillary Thyroid Carcinoma; Lymph Node Metastasis (LNM); Thyroidectomy